Fighting for the Forty-Ninth Star : C. W. Snedden and the Crusade for Alaska Statehood - Cole, Terrence, 1953- (Book collections on Project MUSE., 2010)
When Alaskans in the 1950s demanded an end to ""second-class citizenship"" of territorial status, southern powerbrokers on Capitol Hill were the primary obstacles. They feared a forty-ninth state would tip the balance of power against segregation, and therefore keeping Alaska out of the Union was simply another means of keeping black children out of white schools. C.W. ""Bill"" Snedden, the publisher of America's farthest north daily newspaper, the Fairbanks Daily News-Miner, helped lead the battle of the Far North against the Deep South. Working behind the scenes with his protege, a young atto.